Engineering a platform: The construction of interfaces, users, organizational roles, and the division of labor - Kelkar, Shreeharsh (New media & society, 2018)
Internet “platforms” like Facebook and YouTube often avoid accountability and regulation by claiming that they are mere software infrastructures with little oversight over their users. Scholars in media and communication studies have shown that these platform companies’ control over interface and algorithm design gives them a disproportionately large power, compared to their users, to fundamentally reshape politically salient categories like the “social” or the “innovative.” This article argues that this power of platforms stems from their ability to shape organizational roles and the division of labor. Based on an ethnographic study of the edX organization, I describe how the architects at edX transformed it from an educational company into a platform by building digital interfaces and formatting multiple organizational roles (their own, those of their “users”) to engineer a dichotomy between “software” and “education.” I suggest that platform studies should expand its concept of governance to include the socio-technical-discursive work of engineering organizational roles and the division of labor.